Funcionamento Psicossocial e Cognição na Esquizofrenia: estudo com doentes institucionalizados de longa duração - M. Machado (2005)
Introduction and aims: There is a large number of studies which indicates that cognitive impairments are the major predictors of a worst prognostic either in social function as well as in psychosocial rehabilitation in schizophrenia. The social performance can be divided in three areas: (1) Community Outcome; (2) Social problem solving and (3) Psychosocial skill acquisition. Specifically the community outcome comes along with cognitive functions (mainly verbal memory delayed and executive performance). However, the way in which these deficits influence the patients daily routine, remains uncertain. The challenge of this work is to find specific cognitive processes that are connected with specific social function areas. Method: observational transversal study with 20 male schizophrenic inpatients. For the two major evaluation areas we use the following instruments: Cognition using CFSCE - Conde Ferreira Standard Cognitive Evaluation (a neuropsychological battery of tests developed in CHCF); Social Adaptative Function Evaluation (SAFE). Results and Conclusions: the results with significative correlations allow us to conclude: (1) worst results in cognition appear to have results in a worst social function in instrumental areas. (2) The area that seems to be most affected by cognitive function is "clothing". (3) Five of the six cognitive domains show significative influence in social functioning; (4) the cognitive areas that are most correlated with SAFE are Verbal Comprehension, Language and Communication. Globally, Social Adaptative Function seems to be influenced by cognition in the Attention/Concentration area, which seems to be central and strongly linked with the clinical and social performance. In conclusion, we can say that cognition is correlated with social performance and therefore with community adaptation.